Complex gas hydrate system in a gas chimney, South China Sea. (June 2019) - Ye, Jianliang; Wei, Jiangong; Liang, Jinqiang; Lu, Jingan; Lu, Hailong; Zhang, Wei; ,
Abstract: Gas hydrates and deep-sea cold seeps are of interest to industry and academia for several reasons, including their implications for offshore geohazards and unconventional resources, and for global climate change and carbon cycling. Guangzhou Marine Geological Survey (GMGS) implemented its fifth gas hydrate drilling expedition in the QiongDongNan Sea Area (QDN-SA) of the northern South China Sea (SCS) from June to September 2018. Multidisciplinary investigations, including Logging While Drilling (LWD), pressure and non-pressure coring, gas composition analyses, in situ temperature and permeability measurements, pore water geochemical analyses, and a regional seismic survey, reveal a complex distribution of gas hydrate within a vertical chimney structure. LWD profiles record high resistivity anomalies and high P-wave velocity variations at 9–174 mbsf, suggesting the coexistence of free gas and gas hydrate in the sediment column throughout the investigated gas chimney. Hydrate-bound and void gas is an admixture of methane (70.1%–98.3%) and heavier hydrocarbons (C2 H6 : 0.16%–17.59%, C3 H8 : 0.05%–9.88%, i-C4 H10 : <0.001%–2.06%, n-C4 H10 : <0.001%–0.85%, i-C5 H12 : <0.001%–0.12%, n-C5 H12 : <0.001%–0.02%), indicating a thermogenic origin for the gas. Based on the high content of C2 + hydrocarbons in the gas composition, it is suggested that sII/sH gas hydrate exists in the study area. The gas chimney is interpreted to provide efficient pathways for fluid migration from an intermediate gas reservoir below the BSR to the gas hydrate stability zone (GHSZ). Gas hydrate crystallization decreases the permeability of the sediment, impeding fluid flowing into the upper sediment layers. Bivalve fragments embedded within carbonate rocks were recovered at the seafloor and multiple levels at two main sediment levels of 3mbsf and ∼54mbsf, indicating recurrent seepage activity. Highlights: First results from the 5th gas hydrate drilling expedition in the QiongDongNan Area of the South China Sea in 2018. Gas hydrates co-exist with free gas between 9 mbsf and 174 mbsf at the drilling site. High C2 + (>10%) in the hydrate-bound gas indicate the presence of sII/sH gas hydrates and a thermogenic gas source. Authigenic carbonates with cold seep bivalve fragments at multiple depths indicate recurrent seepage in the past 0.54 Ma.